A CLINICAL STUDY ON GUDUCHI SATTAVA (STARCH OBTAIN FROM STEM OF TINOSPORA CORDIFOLIA) IN MADHUMEHA W.S.R. TO DIABETES MELLITUS TYPE II - Suman, *Kundu; Sukumar, Ghosh; Hazera, Khatun (International Journal of Ayurveda and Pharma Research, 2016)
Madhumeha (Type 2 Diabetes Mellitus) is a global burden. At present, it occupies significant position among non-communicable diseases. It is a major cause of mortality and morbidity in middle age group people. Alterations in metabolism have been main culprit in the pathology of Type 2 Diabetes Mellitus. There are several challenges in diabetes management, including a rising prevalence in urban and rural areas, lack of disease awareness among the public, limited health care facilities, high cost of treatment, suboptimal glycemic control and rising prevalence of diabetic complications. India has to take drastic and urgent steps to develop an integrated national system for early detection and prevention and better management of Diabetes Mellitus. The present clinical study conducted to evaluate the effectiveness of Guduchi sattava in reliving the symptoms of hyperglycemia. Fifty newly diagnosed Madhumeha patients of either sex in the age group of 30-70 years are included in this study. Guduchi sattava (1g daily) are given orally for 90 days with plan water with and without diet restriction and exercise. Type 1Diabetes Mellitus, Diabetes Mellitus with pregnancy, Gestational diabetes etc are excluded here. All patients are evaluated based on clinical features, and laboratory parameters like-blood glucose level, lipid profile and HbA1C. The present study concluded that Guduchi sattava has definite hypoglycemic effect and more effective on fasting glucose level then postprandial glucose along with diet and exercise.